Analysis of tic strategies of the tourist sector in the Meta department after the contingency of COVID-19 - Rodríguez, Aura Luz (2022)
The objective of this article is to evaluate the effectiveness of the use of ICT in the innovation processes with market orientation of entrepreneurs in the tourism value chainin the Department of Meta (Colombia); the level of use of technological tools was identified, as support for organizational processes, promotion, advertising, marketing, customer service and inter- and intra-company communication, and the impact of digital and virtual strategies on customer-oriented innovation management was analyzed; all this contrasting, through a documentary review, the experiences of ICT implementation in the tourism sector, with what was observed in a sample of 50 operators from different links of the value chain, among which are restaurants, hotels, farms agencies, travel agencies and tourist guides, with whom a quantitative and descriptive approximation was achieved through the virtual tools available on the web and based on semi- structured interviews. It is concluded that, compared to the universe of technological possibilities, the regional tourism sector is lagging behind, limiting its strategy to the narrow margins of conventional ICT promotion and dissemination media, allowing barely a meager survival of territorial tourism.